Knowledge and Attitudes About Emergency Contraception Among Married Women in the Eastern Black Sea Region of Turkey - Yeşim Bayoğlu Tekin; Ülkü Mete Ural; Işık Üstüner; Gülşah Balık; Figen Kır Şahin; Emine Seda Güvendağ Güven (Medical Network, 2016)
OBJECTIVE: Emergency contraception (EC) is an effective contraceptive method that can be used after having unprotected intercourse to prevent the implantation of the unintended pregnancy. We aimed to evaluate the knowledge level of reproductive aged women about EC pills and its relation to the contraceptive attitudes and personal characteristics. STUDY DESIGN: A cross-sectional prospective study conducted in a university hospital in Turkey. A questionnaire was given to married women ages 18 to 49 years old. The frequency distribution of dependent (knowledge, attitudes, and beliefs) and independent (age, gravidity, parity, income and education level, contraceptive methods) variables was calculated. RESULTS: Of the 187 women, who completed the survey, 40.8% were aware of EC pills, 35.1% correctly answered regarding the timing of use, and 26.6% reported using EC pills. Negative beliefs about the morning after pill were commonly about adverse effects and lack of experience (62.6% and 45.9%, respectively). The other common reasons for not using EC were described as religious reasons (20.8%) and responsibilities (40.8%). CONCLUSIONS: Awareness and knowledge of EC was low among the women interviewed. The major barriers to use of EC are lack of information and misconceptions about EC. To increase their awareness and dispel negative attitudes, Turkish women need intensive information about EC.